Medan Makna Aktivitas Tangan Dalam Bahasa Skou: The Meaning Field Of Hand Activity In Skou Language - Sitti Mariati (Balai Bahasa Provinsi Papua, 2022)
Language of Skou is located in the northern coastal border area in east of Jayapura. The speakers of Skou are spread in three villages, that are Skou Yambe Village, Skou Mabo Village, and Skou Sae Village. As well other regional languages, Skou language is also a very interesting object of study. As many as the results of Skou language studies, the author has not found any research or study results discuss the meaningful description of Skou language. This study uses descriptive method. Data have been recorded are classified according to its lexical semantics. Furthermore, it is described using componential analysis. This study aims to describe lexemes in Skou based on the meaning field of hand activity in Skou language. Based on data grouping shows that the hand activities are classified into 20 sub meaning fields. That division is based on the purpose of the hand’s own activity. In this study, the meaning field that analyzed are only six sub meaning fields, namely (1) holding, (2) touching, (3) taking, (4) carrying, and (5) putting.